2002
DOI: 10.1136/bmj.325.7371.995
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of fires and related injuries after giving out free smoke alarms: cluster randomised controlled trial

Abstract: Objective To measure the effect of giving out free smoke alarms on rates of fires and rates of fire related injury in a deprived multiethnic urban population. Design Cluster randomised controlled trial. Setting Forty electoral wards in two boroughs of inner London, United Kingdom. Participants Primarily households including elderly people or children and households that are in housing rented from the borough council. Intervention 20 050 smoke alarms, fittings, and educational brochures distributed free and ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 19 publications
2
65
0
Order By: Relevance
“…The Centers for Disease Control and Prevention (CDC)-sponsored Smoke Alarm Installation and Fire Safety Education program recommends the installation of lithium-battery smoke alarms with a hush feature for high-risk households (6,64). DiGuiseppi and colleagues (46) found that families who had their smoke alarm directly installed were much more likely to have a functioning alarm six months later as compared with families who received a voucher for a free smoke alarm. More recently, Gielen and colleagues reported higher rates of participation in a fire department home-visiting program when community health workers provided advanced notice to residents about the upcoming visits (56).…”
Section: Prevention Strategiesmentioning
confidence: 99%
“…The Centers for Disease Control and Prevention (CDC)-sponsored Smoke Alarm Installation and Fire Safety Education program recommends the installation of lithium-battery smoke alarms with a hush feature for high-risk households (6,64). DiGuiseppi and colleagues (46) found that families who had their smoke alarm directly installed were much more likely to have a functioning alarm six months later as compared with families who received a voucher for a free smoke alarm. More recently, Gielen and colleagues reported higher rates of participation in a fire department home-visiting program when community health workers provided advanced notice to residents about the upcoming visits (56).…”
Section: Prevention Strategiesmentioning
confidence: 99%
“…Previous studies have identified that there are barriers to maintaining passive home safety measures (Stone et al, 2007;DiGuiseppi et al, 2002) and it is important to establish these barriers in relation to fire door installation and maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…DiGuiseppi et al 125 carried out a cluster-randomised controlled trial of the impact of providing free smoke alarms on the incidence of fires and related injuries in a deprived inner city population. A later trial explored variation in the prevalence of working smoke alarms by type of alarm 41 and a qualitative study was carried out to explore barriers and facilitators to the use of smoke alarms.…”
Section: Health Protection and Improvement Interventions Are Sometimementioning
confidence: 99%